Thermal expansion and thermal conductivity of RT2 (R: Gd, Dy, Er; T: Al, Ni) intermetallic compounds for magnetic refrigerator. Issue 1 (April 2021) - Watanabe, S; Komatsu, S; Futatsuka, K; Kumazawa, N; Matsumoto, K; Kamiya, K; Takeya, H; Numazawa, T
Abstract: Highly efficient hydrogen liquefaction is required for upcoming hydrogen energy society. Magnetic refrigeration is expected as a method to realize efficient hydrogen liquefaction, and the performance depends on properties of magnetic materials. RT 2 ( R : rare-earth; T : Al, Ni) Laves phase intermetallic compounds with a second-order magnetic phase transition are one of the promising magnetocaloric materials. Thermal expansion, magnetostriction, and thermal conductivity of ErAl2, DyNi2, DyAl2 and GdNi2 were measured in magnetic fields using polycrystalline samples because of the important properties for practical use in a magnetic refrigerator. Thermal expansions showed anomalies at the magnetic transition temperature. However, those in 0 T were nearly the same as copper. Magnetostriction were not as large as magnetocaloric materials with a first-order magnetic phase transition such as TbMn2 . Thermal conductivities in 0 T were almost in agreement with the literature data, and magnetic field dependence was small. These results indicate that RT 2 compounds are suitable as magnetic refrigerants for hydrogen liquefaction in practical use.